2015
DOI: 10.1530/rep-14-0438
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the intrafollicular thiol–redox system in infertile women with endometriosis

Abstract: The aim of this study was to compare intrafollicular biomarkers of thiol-redox system and chronic inflammation in infertile patients with and without endometriosis, and examine correlations between biomarkers and IVF outcomes. The study included 65 patients receiving IVF: 31 patients with endometriosis vs 34 patients without endometriosis. Follicular fluid (FF) was obtained from a single-dominant follicle during oocyte retrieval and stored at K70 8C. Malondialdehyde, superoxide dismutase, glutathione (GSH), gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 53 publications
0
37
0
6
Order By: Relevance
“…In addition, the concentrations of critical antioxidants are aberrantly expressed in endometriosis patients. Levels of glutathione are diminished in the follicular fluid of women with endometriosis [93] and low levels of other antioxidants including vitamin A, C and E were found to be significantly reduced in the intra-follicular fluid of women with endometriosis associated infertility compared to women with tubal infertility [92]. As expected, higher levels of glutathione have been correlated with higher quality embryos [93].…”
Section: Implication Of Immune Dysfunction On Oxidative Stressmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, the concentrations of critical antioxidants are aberrantly expressed in endometriosis patients. Levels of glutathione are diminished in the follicular fluid of women with endometriosis [93] and low levels of other antioxidants including vitamin A, C and E were found to be significantly reduced in the intra-follicular fluid of women with endometriosis associated infertility compared to women with tubal infertility [92]. As expected, higher levels of glutathione have been correlated with higher quality embryos [93].…”
Section: Implication Of Immune Dysfunction On Oxidative Stressmentioning
confidence: 87%
“…Levels of glutathione are diminished in the follicular fluid of women with endometriosis [93] and low levels of other antioxidants including vitamin A, C and E were found to be significantly reduced in the intra-follicular fluid of women with endometriosis associated infertility compared to women with tubal infertility [92]. As expected, higher levels of glutathione have been correlated with higher quality embryos [93]. Correspondingly, high concentrations of oxidative stress metabolites and lower concentrations of antioxidant molecules are associated with less successful IVF treatments [92].…”
Section: Implication Of Immune Dysfunction On Oxidative Stressmentioning
confidence: 99%
“…Furthermore, endogenous antioxidant compounds are also disrupted in women suffering from endometriosis. Specifically, lower plasma SOD concentration, lower follicular fluid vitamin C levels and imbalanced intrafollicular thiolredox system were detected in infertile women with endometriosis, in comparison with controls (207,208). In a study by Mier-Cabrera et al, when a high-antioxidant diet was administered in women with endometriosis, peripheral oxidative stress markers, including MDA and lipid hydroperoxides, were significantly attenuated and antioxidant markers, specifically SOD and GPx, were enhanced (209).…”
Section: Endometriosismentioning
confidence: 96%
“…The custom-designed six-plex kit included reagents to detect human cytokines IL-1β, IL-6, IL-8, IL-15, IL-18 and tumour necrosis factor-α (TNF-α). We have chosen these cytokines as previous studies have shown dysregulation of these factors in endometriosis in serum [6], peritoneal [9] and follicular fluid of conventional, gonadotropin-stimulated IVF [6,[16][17][18], suggesting these factors to be associated with endometriosis. The Bio-Plex® assay was performed according to the manufacturer's instructions and has previously been described [13].…”
Section: Multiplexed Cytokine Determinationsmentioning
confidence: 99%